EFFICIENT SYNTHESIS OF AN EPOXY ALCOHOL, A KEY INTERMEDIATE FOR LTA4 SYNTHESIS - PARK, H; LEE, YS; SHIM, SC (KOREAN CHEMICAL SOC, 1992)
An efficient and very short synthesis of epoxy alcohol 5, a key intermediate for leukotriene synthesis, was described. The key reaction involves the regioselective benzylidene acetal formation from methyl 5,6,7-trihydroxyheptanoate 1.
Keywords: ACID; LEUKOTRIENES; SELECTIVITY; ESTER